KONDISI FAKTOR FISIK RUMAH YANG TERKAIT DENGAN TUBERKULOSIS PARU DI PUSKESMAS BANDARHARJO KOTA SEMARANG - Ekky Resha Pradita; Suhartono Suhartono; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Tuberculosis is a disease which remains the global main concern. Tuberculosis is an infectious disease caused by the bacillus Mycobacterium tuberculosis. The disease is transmitted through the air (droplet nuclei) when people infected tuberculosis cough or sneeze. Puskesmas Bandarharjo is a health center with the highest Tuberculosis patients in Semarang City in 2017 in which the number of case was 103 per 100.000 population. This study aims to describe the characteristics of respondents and analyze the relationship between the level of lighting, the width of the house ventilation, type of wall and type of floor with the level of humidity. This research used observational analytic research with case control approach. The sample in this study was 84 people consisting of 42 cases and 42 controls. The data analysis used chi square test with confidence level of 95%. The results of this study show that the average age of respondents is 39 years consisting of 23 male (54.8%). The dominant type of work of the most respondents is entrepreneur. The results of chi square found the house lighting level (p value: 0,000), house ventilation area (p value: 0,000), wall type (p value: 0,672) and floor type (p value: 0,653). The conclusion of this study there is a relationship between the level of lighting and the area of home ventilation with the level of humidity of the house.